Intervensi Menulis Ekspresif untuk Menurunkan Kecemasan Menjalani Kemoterapi pada Pasien Penderita Kanker Payudara - Nurainina Fildzah Abdurrahman; Sitti Murdiana; Ahmad Ridfah (Universitas Kristen Maranatha, 2020)
Individuals who are diagnosed with breast cancer will cause emotional reactions in the form of anxiety. Breast cancer sufferers will experience anxiety in different situations, which is when undergoing chemotherapy treatment. This study aims to determine the role of expressive writing interventions to reduce anxiety undergoing chemotherapy in patients with breast cancer. It applied quasy experimental design, one-group pretest-postest design. The subjects of this study were 2 patients with breast cancer who were undergoing chemotherapy treatment. The measuring instrument used in this study is State-Anxiety scale which refers to the theory of Spielberger. The analysis technique used is visual inspection analysis. The research proves that expressive writing can reduce the anxiety of andergoing chemotherapy in patient with breast cancer. The implication of this research is expressive writing can be used as a medium to reduce perceived anxiety. Keywords: Anxiety, chemotherapy, expressive writing.